2013
DOI: 10.2169/internalmedicine.52.9584
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Track Microbubble Flow Signals on Contrast-enhanced Ultrasound with Perflubutane Following Percutaneous Liver Biopsy

Abstract: Objective It is important to detect post-liver biopsy hemorrhage early and confirm hemostasis in the clinical setting. Contrast-enhanced ultrasound (CEUS) is a sensitive and highly specific tool for detecting active bleeding. The aim of this study was to investigate the rate of detection of track microbubble flow signals on CEUS with perflubutane following liver biopsy and to assess the disappearance of these signals.Methods Microbubble flow signals along the needle track on CEUS were examined in 100 patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
1
4
0
1
Order By: Relevance
“…There are just few studies in the literature conduced where it is demonstration on CEUS. 1,2 We confirm that intraparenchymal flow signal along needle tract is also possible to be evaluate with the ultrasound power Doppler (Figure 1A-D) and is called "patent track" sign. The presence of either pulsatile arterial or venous waveforms in the patent track is not statistically associated with the severity of hemorrhage.…”
supporting
confidence: 68%
“…There are just few studies in the literature conduced where it is demonstration on CEUS. 1,2 We confirm that intraparenchymal flow signal along needle tract is also possible to be evaluate with the ultrasound power Doppler (Figure 1A-D) and is called "patent track" sign. The presence of either pulsatile arterial or venous waveforms in the patent track is not statistically associated with the severity of hemorrhage.…”
supporting
confidence: 68%
“…A total of 12 studies (all case series) fall into this miscellaneous section, which includes 4 categories of CEUS assisted procedures: (1) US‐guided abscess drainage; (2) US‐guided percutaneous nephrostomy; (3) US‐guided biliary interventions; and (4) hepatic and splenic hemorrhage. In the first 3 categories, a diluted contrast solution (ie, 0.1 mL of SonoVue in 20 mL of saline) is injected directly in the catheter or needle to visualize the exact location of the cavity or tissue around the catheter or needle tip: so‐called intracavitary CEUS.…”
Section: Resultsmentioning
confidence: 99%
“…Intravenous use of CEUS to detect and guide percutaneous treatment of splenic and hepatic hemorrhage or lesions after trauma or biopsy has been reported in 4 series, but only in 2 series was another imaging technique (CT) used as the reference standard, which resulted in a detection rate of 100% in both . Three of the studies reported on CEUS‐guided percutaneous treatment of hemorrhage .…”
Section: Resultsmentioning
confidence: 99%
“…CEUS may be used to: a) Diagnose and monitor all stages of bleeding related to interventional procedures and guide percutaneous local application of hemostatic drugs [491,492]. b) Improve breast cancer staging by identifying and guiding biopsy of the sentinel node after intradermal CEUS if axillary B-mode US is normal [413].…”
Section: Further Benefits From Ceus In Interventional Usmentioning
confidence: 99%